Miniinvazivní odběr spongiózních štěpů v traumatologické indikaci – experimentální část studie - Látal, P; Štiková, Z; Tříska, Z; Šperl, J; Kloub, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2020)
PURPOSE OF THE STUDY Our experimental study presents a set of bone grafts harvested by a minimally invasive procedure from selected deceased donors. Our objective was to compare the concentration of red bone marrow in the cancellous bone harvested in this way from selected regions with the reference harvesting from the iliac crest. Thus, the potential of grafts to heal complicated fractures or non-unions is assessed. MATERIAL AND METHODS The Hospital Department of Pathology provided 10 cadaver preparations - 7 male and 3 female for the experiment. In the process of selection, the age limit was 18-50 years, the other exclusion criteria were severe injuries and burning to death as mechanisms affecting the condition of the skeletal system, bone diseases except for osteoporosis, and malignant diseases. From each preparation, a total of 12 samples of cancellous bone tissue were harvested from pre-defined 6 harvest sites bilaterally - proximal humerus, proximal ulna, greater trochanter of proximal femur, distal femur, proximal tibia and from the reference region of the iliac wing. The grafts were harvested using a 10 mm bone cutter. In total, 120 samples of cancellous bone of the determined diameter and uniform length of 30 mm were obtained. The obtained preparations were laboratory processed, fixed, decalcified and hematoxylin-eosin stained. The samples were assessed microscopically. The share of the bone tissue and cancellous bone was expressed as a percentage. Determined as a healing potential parameter was the concentration of red bone marrow and its ratio to the yellow bone marrow was stated. The hypothesis was tested using the ANOVA analysis of variance. RESULTS The highest concentration of red bone marrow was observed in cancellous grafts harvested from the iliac wing with 34.95%, followed by greater trochanter of proximal femur with 31.7%, distal femur with 26.9% and proximal humerus with 21.9%. Its concentration was negligible in proximal tibia with 2.55% and proximal ulna with 0.15%. By ANOVA statistical method the values of reference samples from the iliac wing and greater trochanter of the femur, distal femur and proximal humerus were compared. The differences are not statistically significant - P 0.60, 0.48 and 0.34 (p < 0.05). No significant differences were found in the concentration of red bone marrow. Statistically compared were also the values of reference samples from the iliac wing and proximal tibia, proximal ulna. This difference is statistically significant - P 0.0008 and 0.0002 (p <0.05). Thus, the difference in the concentration of red bone marrow is obvious. DISCUSSION The aforementioned results suggest that the greatest potential to heal will be achieved with the use of bone grafts from the iliac wing region, followed by greater trochanter of the femur, distal femur and proximal humerus. When testing the hypothesis by the ANOVA method, the detected differences between the selected harvest regions are not statistically significant. Therefore, the iliac wing grafts can be used in practice just as the material from greater trochanter of the femur, distal femur or proximal humerus, which is of equal quality. The other regions, proximal tibia and ulna, contain only minimum concentration of red bone marrow. CONCLUSIONS The experimental study comparing the concentration of red bone marrow in grafts harvested using a minimally invasive procedure from the region of greater trochanter, distal femur and proximal humerus concluded that these samples are comparable with the grafts from the iliac wing. The grafts harvested from proximal tibia and proximal ulna show only negligible concentration of red bone marrow and their use in clinical practice is disputable. The benefits of our experimental study for treatment shall be further evaluated in a clinical study. Key words: bone marrow, stem cells, bone healing/orthobiologics, new technology assessment, autograft harvesting.
Keywords: transplantace kostní dřeně; trabekulární kostní tkáň; Animals; transplantace kostí; tibie; Bone Marrow Transplantation; Ilium; femur; Female; Tibia; zvířata; mužské pohlaví; os ilium; Male; Cancellous Bone; Bone Transplantation; Femur; ženské pohlaví